Eski Çağ Tarihi ve Uygarlıkları - Çalış, Said Mübin; Çayır, Murat; Ayyıldız, Sedef; Tuncer, Hasan; Yılmaz, Cemal; Topaloğlu, Yasin; Çoban, Hacı; Günel, İlknur and Temizkan, Meltem and Tekin, Murat and Ören, Hacı and Ateş, Aysel and Soğandereli, Fatma and Özdemir, Muammer and Arslan, Yavuz and Doğancı, Kamil (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-